The Role of Sustainability Reports in Building Stakeholder Trust: A Case Study of Bank Artha Graha Internasional - Ryan Rajasa Pratama Rifkinnanda Sukma Putra; Regina Jansen Arsjah (Utan Kayu Publishing, 2025)
This research analyzes the role of sustainability reports in strengthening relationships with stakeholders, with a case study of Bank Artha Graha Internasional. Using a qualitative approach and case study method, the study involved in-depth interviews with management, employees, customers, and regulators (three individuals from each group, totaling 12 people), and document analysis, including Bank Artha Graha Internasional's sustainability report. The findings indicate that sustainability reports serve as a strategic communication tool that not only enhances corporate transparency but also strengthens stakeholder trust. Bank Artha Graha Internasional utilizes these reports to showcase their sustainability initiatives, such as Corporate Social Responsibility (CSR) programs and green financing, which directly contribute to improving the company's positive image among stakeholders. The results also show that stakeholders, particularly investors and regulators, consider sustainability reports an important indicator in their decision-making processes. The study concludes that sustainability reports play a significant role in building closer relationships with stakeholders through increased transparency, accountability, and corporate communication. Furthermore, a well-prepared sustainability report can strengthen the company's legitimacy in society and provide a long-term competitive advantage.